Influence of Different Synchronization Protocols on Fertility Response in Surti Does - Sharma, Hitendra C.; Khasatiya, Chandubhai T.; Tyagi, Kuldeep K.; Modi, Lalit C. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
This study was carried out to assess the influence of different estrus synchronization Protocols on fertility response in Surti does based on litter size, fecundity and twining rate. Thirty does were selected and divided into five equal groups (n=6 in each). Does of G1 group were treated with intra-vaginal progestagen sponges (IVPS) for 11 days. Does of G2 group received the same IVPS sponge for 11 days and exposure of sexually active apronized buck during the treatment period. Does of G3 group were treated as per G1 group along with i/m injection of PGF2α analog (125 μg, Cloprostenol) at the time of sponge removal. Does of G4 group were subjected to the buck effect and exposed to a sexually active patronized buck for 11 days, and does of G5 group was kept as a control without any treatment for 11 days. It was found that, none of the synchronization Protocols had significant effect on litter size, fecundity, and incidence of multiple kid birth and sex ratio in Surti does.